1984
DOI: 10.1159/000183242
|View full text |Cite
|
Sign up to set email alerts
|

Rising Serum Digoxin without Further Dosage in Acute Renal Failure

Abstract: A 73-year-old man was given a total of 1 mg of digoxin intravenously over 3 days, close to the time that he developed acute renal failure with oligo-anuria. He received no cardiac glycosides before or after this 3-day period. 2 days after the last dose, the serum digoxin concentration (SDC) was 2.9 ng/ml, yet a peak value of 4.2 ng/ml was reached only 11 days later. The SDC remained above 2 ng/ml for another week, until urine output began to increase appreciably. As renal function improved, the SDC gradually f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The individual isoforms of Na,K-ATPase have been shown to possess differing affinities for binding of digitalis, ouabain, and their respective deglycosylated derivatives (11,12). The importance of characterizing the molecular and physical properties of DLIF is further underscored by the linkage observed between increased DLIF concentrations in blood and clinical or pathological conditions associated with altered ion-transport homeostasis such as: renal failure (13,14), hepatic failure (15), pregnancy (16), neonatal development (17,18), diabetes-and exercise-induced stress (19,20), and hypertension (21)(22)(23). The source of digitalis-like factors in a hormone-secreting tissue such as the adrenal, presence in blood, and the distribution of likely receptors in target tissues suggest the likely possibility of a new hormonal axis linking the adrenal cortex, endogenous digitalis-or ouabain-like factors, and sodium pump activity (5,24).…”
mentioning
confidence: 99%
“…The individual isoforms of Na,K-ATPase have been shown to possess differing affinities for binding of digitalis, ouabain, and their respective deglycosylated derivatives (11,12). The importance of characterizing the molecular and physical properties of DLIF is further underscored by the linkage observed between increased DLIF concentrations in blood and clinical or pathological conditions associated with altered ion-transport homeostasis such as: renal failure (13,14), hepatic failure (15), pregnancy (16), neonatal development (17,18), diabetes-and exercise-induced stress (19,20), and hypertension (21)(22)(23). The source of digitalis-like factors in a hormone-secreting tissue such as the adrenal, presence in blood, and the distribution of likely receptors in target tissues suggest the likely possibility of a new hormonal axis linking the adrenal cortex, endogenous digitalis-or ouabain-like factors, and sodium pump activity (5,24).…”
mentioning
confidence: 99%
“…Explanations considered and excluded at the time included medication error, sur reptitious ingestion or assay interference by a concomi tant drug. Based on previous reports, assay interference by an endogenous digoxin-like immunoreactive sub stance^) [ 1 ] and/or a decrease in the volume of distribu tion of digoxin due to diminished tissue uptake in pro gressive renal dysfunction [3,7] were considered the most likely explanations. An endogenous immunoreac tive substance(s) has been noted in similar patients but usually has accounted for less than 2 ng/ml o f 'apparent' digoxin [1,8], Our patient had increases in 'apparent' digoxin of almost double the greatest value previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports [2,3] have noted marked increases in serum digoxin concentration despite discontinuation of the drug in two patients with acute renal failure. An alteration in the volume of distribution of digoxin has been suggested to be the cause in one of these patients [3], Herein we describe a patient with renal and hepatic dysfunction in whom a marked increase in apparent serum digoxin concentration was observed despite dis continuation of the drug. This increase (peak value 8.6 ng/ml), however, was not associated with electrocardio graphic findings consistent with increased digoxin effect or toxicity.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Endogenous digoxin-like substance(s) (EDLS) detectable by radioimmunoassay for digoxin have been found in the serum of neonates [16,19], in patients with renal dis ease [6,8] and in essential hypertensives [4], In all cases the subjects shown to have EDLS circulating had not previously been exposed to digoxin or to any other cardiac glycoside. High EDLS levels have also been Previous studies have suggested that EDLS levels in the neonate stem from en dogenous production (secretion) of these as yet unidentified compounds [17], In the present series we wished to assess whether the course of late pregnancy affected neona tal EDLS levels.…”
Section: Introductionmentioning
confidence: 99%